Thermal inactivation analysis of water-related pathogens in domestic hot water systems. Issue 2 (19th June 2017) - McCarton, Liam; O'Hogain, Sean
Abstract : This study aims to investigate whether hot water systems supplied with harvested rainwater present an increased risk to health over hot water systems supplied with potable mains water. It reviews previous studies investigating the health effects of utilising rainwater within domestic systems. The main risk to public health of mains-supplied hot water systems is the operation, maintenance, age, location and temperature of the system. Rainwater-harvesting systems contain an inherent water treatment train consisting of flocculation, settlement, sorption and bioreaction, and stored rainwater quality improves as metal and chemical contaminants settle to form sludge. Laboratory experiments were conducted using a variety of water-related bacteria to determine the time required to reduce a bacterial population by 90% at a given temperature. The results of this study show that after 5 min of exposure at 60 and 55°C, respectively, Salmonella, Pseudomonas aeruginosa and total viable count at 22 and 37°C concentrations were reduced to zero. Irish standards require hot water systems to be maintained at temperatures at or above 60°C. The conclusion from this pilot study is that hot water systems supplied with harvested rainwater do not present an increased risk to health over hot water systems fed with mains water.